2016
DOI: 10.1111/asj.12612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing an active dry yeast product on rumen microbial community composition and on subsequent rumen fermentation of lactating cows in the mid‐to‐late lactation period

Abstract: The effects of supplementing feed of cows in mid-to-late lactation with an active yeast product (Actisaf Sc 47) were evaluated using 15 Holstein cows in a replicated 3 × 3 Latin square design. The animals were fed a mixed ration with 33% neutral detergent fiber, consisting of timothy hay (29.8%), a commercial concentrate (70.0%) and commercial calcium triphosphate (0.2%), twice daily to meet 105% of their energy requirement. Yeast supplement was set at 0, 5 and 10 g per day over 21-day periods, each of which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
6
18
1
Order By: Relevance
“…A linear decline in MCP values was observed with increasing levels of UM or FM (p < .01), and quadratic effects of the replacement ratio were observed in both substrates (p < .01). Ruminal MCP provides 40-80% of the protein needs for ruminants (Uyeno et al 2017). The higher MCP with not-different ammonia concentration in the FM compared to the UM indicates that the fermented YWL promoted the ability of rumen microorganisms to synthesise MCP from ammonia-N and enhanced the efficiency of protein synthesis.…”
Section: In Vitro Rumen Fermentation Parametersmentioning
confidence: 94%
See 2 more Smart Citations
“…A linear decline in MCP values was observed with increasing levels of UM or FM (p < .01), and quadratic effects of the replacement ratio were observed in both substrates (p < .01). Ruminal MCP provides 40-80% of the protein needs for ruminants (Uyeno et al 2017). The higher MCP with not-different ammonia concentration in the FM compared to the UM indicates that the fermented YWL promoted the ability of rumen microorganisms to synthesise MCP from ammonia-N and enhanced the efficiency of protein synthesis.…”
Section: In Vitro Rumen Fermentation Parametersmentioning
confidence: 94%
“…With increasing levels of UM and FM, the ammonia-N concentration decreased linearly (p < .01). Rumen ammonia-N is the final product of the microbial decomposition of N-containing substances (Uyeno et al 2017). The CP level and digestibility of FM were proved to be higher than those of UM (Yao et al Table 3.…”
Section: In Vitro Rumen Fermentation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of yeast in ruminants reduces subclinical acidosis (Bach et al 2007, however, the supplementation of yeast had no effect on the pH during the experimental induction of acute acidosis in cattle (Vyas et al 2014 b ). Uyeno et al (2017) suggest that effects of supplementing live yeast to cows in mid-to-late lactation may be limited to microbial composition and fermentation characteristics in the rumen.…”
Section: Zootechnical Additives and Vaccinesmentioning
confidence: 99%
“…In addition, supplementation with yeast culture was shown to increase total and cellulolytic bacterial numbers in the rumen fluid of rumen-cannulated sheep [25].Callaway and Martin[3] reported that yeast culture provides soluble growth factors (i.e., organic acids, B vitamins, and amino acids), which stimulate the growth of ruminal lactate-utilizing and cellulolytic bacteria. An increase in fibrolytic bacterium, Fibrobacter, was also observed in the rumen fluid of cows supplemented with LY[37]. Other studies have reported that yeast products reduced redox potential in the rumen in lambs[5] and sheep[20], suggesting that LY is capable of oxygen scavenging and provides improved conditions for the growth and activity of anaerobic rumen bacteria, particularly for highly oxygen sensitive species, such as cellulolytic bacteria.…”
mentioning
confidence: 80%